Bailoterapia, factor influyente para la coordinación rítmica en los estudiantes de la unidad educativa Lauro Damerval n° 1 de la ciudad de Loja - Saavedra Ramos, Rodrigo Andres (2016)
This paper is titled: Dance Aerobics, rhythmic coordination influential for students in the educational unit Lauro Damerval No. 1 of the city of Loja factor. The central problem is the bailoterapia, influential factor for rhythmic coordination students Damerval Lauro educational unit No. 1 of the city of Loja. The overall objective is to implement a program of physical exercises and methodological workshops to improve coordination in rhythmic dance therapy students in the Educational Unit "Lauro Damerval". The methods used in the research were logical historical analysis and synthesis, induction and deduction. The sample used was the entire population of the class as are 30 students. The most important results achieved are: It is important that the teacher talks related to the importance of dance therapy for the welfare and health practitioners. The teacher should make promotion in the school community about the bailoterapia is from music coordination of movements, doing demonstrations allowing observation of students, motivating him to practice this exercise. You must also create a set of practical exercises coordination to create habits and in turn facilitate the smooth implementation of exercises for bailoterapia. And search methods, meaningful learning and coordination in general to contribute to achieving good coordinative movements of dance therapy.